2022
DOI: 10.1002/jwmg.22242
|View full text |Cite
|
Sign up to set email alerts
|

Coyote and porcupine spread Russian olive seeds through endozoochory

Abstract: Russian olive (Elaeagnus angustifolia) is an invasive tree that has spread throughout much of the western United States. The mode of seed dispersal occurs by hydrochory and possibly by birds. Seed dispersal by frugivorous mammals has not been investigated.Between 15 October and 4 November 2020, we walked through Russian olive windbreaks in western North Dakota, USA, and surveyed for mammal scat, and found 10 coyote (Canis latrans) and 54 porcupine (Erethizon dorsatum) scats that contained intact Russian olive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Because these ecosystems did not evolve with a large abundance of fruit-bearing trees in the riparian corridor, olive can alter aquatic food webs. Olive fruit is known to be an important food resource for many birds and mammals (Campbell & West, 2022;Edwards et al, 2014), and we observed many terrestrial vertebrates utilizing olive fruits in their diet, including bears, raccoons, squirrels, mice, coyotes, horses and turkeys and many other bird species (Cheek, pers. observation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because these ecosystems did not evolve with a large abundance of fruit-bearing trees in the riparian corridor, olive can alter aquatic food webs. Olive fruit is known to be an important food resource for many birds and mammals (Campbell & West, 2022;Edwards et al, 2014), and we observed many terrestrial vertebrates utilizing olive fruits in their diet, including bears, raccoons, squirrels, mice, coyotes, horses and turkeys and many other bird species (Cheek, pers. observation).…”
Section: Discussionmentioning
confidence: 99%
“…Many catfishes act as dispersal agents for terrestrial plants (Correa et al, 2007), and catfish can transport viable seeds and increase germination potential of other riparian plants such as red mulberry ( Morus rubra ) and swamp privet ( Forestiera acuminata ) (Chick et al, 2003). Olive receives seed dispersal and germination benefits through interactions with frugivorous mammals and birds (Campbell & West, 2022; Edwards et al, 2014) but more research is needed to determine if catfish can provide this benefit. If catfish promote reproductive success of olives, the interaction could represent a mutualism in which food and dispersal are exchanged to the benefit of both participants (sensu Silknetter et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding seed dispersal, zoochory may accelerate tree invasion through external or internal transport mechanisms. For example, the transport of seeds of the Russian olive ( Elaeagnus angustifolia L.) by mammals and possibly also by birds, was reported to accelerate its invasion across the western USA (Campbell and West, 2022). At the same time, seed predation may control plant invasion.…”
Section: The Alien Challenge: Control and Management Of Invasive Tree...mentioning
confidence: 99%